Comprehensive Textbook of Psychiatry / II Vol. 2 - Freedman, Alfred M. et al (Williams & Wilkins, 1975)
This book contain a wealth of new information and updated for every psychiatric practice$1! =s
Keywords: Mental disorders; Non-Fiction; Psychiatry-History